Entrelaçando Musicoterapia E Psicolinguística: Estudo De Caso Sobre A Disartria (PERcursos Linguísticos, 2022)
This study came from the interest in understanding the fall of syllables in the atypical speech. Our subject (RA.) was the victim of a car accident at the age of 28, affected by a cranial trauma, leaving dysarthria as a sequel. In the study, we follow the theoretical-methodological studies of Psycholinguistics and Music Therapy. For the longitudinal study, we carried out activities that aimed to recover and stimulate speech through Music Therapy. With dysarthria, the speech duration of RA suffered alterations, becoming accelerated in an almost unintelligible way, as a result of which he presented an undue fall of syllables. Our results showed that after AR's participation in ten Music Therapy sessions there was an improvement in his speech as he presented less deletion of unstressed syllables. In addition, RA was also subjected to two interviews, in the last one, which was held after the ten sessions, RA produced 50% fewer sentences with syllable deletion compared to the initial interview. In this way, we demonstrate that with the Music Therapy intervention, RA presented a better perception of his own pronunciation of unstressed syllables as well as he began to avoid deletion in inappropriate contexts according to his dialect.